THE INFLUENCE OF JOB TRAINING AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE IN THE GENERATION Z WORKFORCE - Cahyani, Fitria; Fauzi, Achmad; Faslah, Roni (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of job training and work experience on employee performance in the Generation Z workforce in Bogor City. This research uses a quantitative method with a survey design. The research population is Generation Z employees in Bogor City, with a sample of 168 respondents selected using purposive sampling technique. The results showed that job training has a positive and significant influence on employee performance. Work experience also has a positive and significant effect on employee performance. Simultaneously, job training and work experience contribute significantly to improving the performance of Generation Z employees. These findings confirm the importance of human resource management through effective training and relevant work experience to improve employee productivity.